2018
DOI: 10.12669/pjms.343.14392
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Management of Neglected Developmental Dysplasia of Hip (DDH): 8-years’experience with single stage triple procedure

Abstract: Objective:To document the clinical presentation of neglected DDH and evaluate the outcome of triple procedure.Methods:It was a descriptive case series study, conducted at the Department of Orthopedic Surgery, National Institute of Rehabilitation Medicine (NIRM), Islamabad over a period of 8-years. It included children aged >1 and <9 years who underwent the triple procedure of open reduction, femoral shortening and Salter’s osteotomy. Clinical evaluation was performed using McKay’s criteria. Tonnis classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The goal of surgery is to reposition the femoral head and restore normal anatomy to prevent long-term complications such as pain, difficulty walking, and arthritis. However, other studies conducted in Pakistan, have reported non-operative approaches to be effective as well, particularly in mild cases [ 16 ]. This is because they are less invasive and have fewer risks than surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of surgery is to reposition the femoral head and restore normal anatomy to prevent long-term complications such as pain, difficulty walking, and arthritis. However, other studies conducted in Pakistan, have reported non-operative approaches to be effective as well, particularly in mild cases [ 16 ]. This is because they are less invasive and have fewer risks than surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In our country, as there is no screening program for at-risk children, the mean age of presentation is above 2 years as reported in previous studies. (10)(11)(12) . Therefore, our sample size was small and about 20 hips were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic explanations may be the cause for the higher frequency in female children and those with a positive family history. An increased incidence of breech deliveries, advanced maternal age, postmaturity, oligohydramnios, or any other crowded intrauterine situation are examples of mechanical factors [ 8 ]. Compared to the healthy side, there is less abduction in hip dislocations.…”
Section: Introductionmentioning
confidence: 99%